Does Perceived Organizational Support (Pos) Serve as a Prerequisite or Organizational Citizenship Behavior (Ocb) Among Employees Working at a Manufacturing Company in Banjarmasin? - Rahmatillah, Vellynda Aisyah; Kusmaryani, Rosita Endang (World Psychology, 2025)
Many employees today tend to focus solely on their main tasks without engaging in extra-role behaviors, which may hinder overall organizational effectiveness. These extra-role behaviors are commonly referred to as Organizational Citizenship Behavior (OCB), which play a significant role in supporting organizational success. One factor that can influence OCB is Perceived Organizational Support (POS), or the extent to which employees feel that their organization values their contributions and cares about their well-being. This study aimed to examine POS as a predictor of OCB among employees in a fabrication company in Banjarmasin, both overall and across each OCB dimension. The study involved 144 employees selected through simple random sampling. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results showed that POS significantly predicts OCB, both in general and within each dimension. These findings highlight the importance of enhancing POS to foster OCB among employees. Companies are encouraged to appreciate employee efforts, recognize contributions, and attend to employee welfare. Strengthening POS can create a supportive work environment that motivates employees to go beyond their formal job roles, ultimately contributing to improved organizational effectiveness and performance.